The Effect of Doxorubicin on ABC Transporter Gene Expression in Triple Negative Breast Cancer - Heald, Robyn (Auckland University of Technology, 2021)
Breast cancer is the single foremost killer of women in the world today, and of this triple negative breast cancer (TNBC) is the most clinically aggressive kind. TNBC impacts roughly 15% of the worlds breast cancer cases and in New Zealand, having the highest rate of breast cancer incidence in the world. Since there is currently no TNBC specific treatment, the majority of people diagnosed with this subtype are often faced with treatment such as chemotherapy and radiation, this being the gold standard of treatment for these tumours. However, in many cases surgical excision of the main tumour mass in conjunction with said therapy is necessary. Surgical removal, as can be common and in fact one of the best therapeutic options for TNBC, poses a few issues. Among these is the likelihood of this subtype of cancer to metastasise. It is for this reason that TNBC tumours are characteristic of a high mortality rate. A considerably higher one than other breast cancers. Most vitally, however, a diagnosis can often be poor for TNBC patients and low survival rates are likely, due to a high incidence of chemotherapeutic resistance in TNBC tumours. Typically, the cells within the tumours of all types develop chemoresistance through several different gene expression changes to regulate and defend themselves from cytotoxic agents. TNBC is no exception to this and by altering the expression of genes responsible for transport proteins (which are embedded in the cell membrane the cells) can increase the efflux of chemicals out of the cell. Functionally this serves to remove the toxic substrate before it has chance to affect the cells. The possibility that ATP-binding cassette (ABC) transporters could be targeted by drugs to make chemotherapy more efficacious in resistant cells could change the mortality rate for cancer patients. This is particularly useful whilst more direct therapeutic options not reliant on non-specific cell death and with fewer dangerous side-effects are researched and trialled. To explore this, expression analysis of a host of genes related to ABC transporter proteins was conducted. The outcome of which was previously observed, in part, in broader spectrum studies to show some varied gene regulation in response to treatment over time with chemotherapy. The experiment required TNBC cells to be induced into a state of resistance which from previous research had been shown to require at least 3 months of treatment of the cells at a dosage in accordance with the IC50 of the drug for the specific cell line in use. The cells used were MDA-MB-231 cells and the corresponding drug, doxorubicin. The cells, after three treatment cycles with the drug doxorubicin at a concentration of 1.24µM, had total RNA extracted before said RNA was converted to cDNA and expression quantities recorded using quantitative real-time polymerase chain reaction (RT-qPCR). The data from this revealed a significant decrease in the expression of ABCG2, a xenobiotic transporter known to be responsible for removing foreign chemicals from the cells. A decrease in expression of significance was also observed in the gene ABCC2. This gene is commonly referred to as multidrug resistance protein 2 (MRP2) and as with ABCG2, it is expressed by cells to promote the clearance of drugs from the cytoplasm. Other genes showed a relative fold increase in expression when compared with reference genes, but no obvious effect was observed over treatment. Studies in this field typically report cellular tolerance and development of multi-drug resistance (MDR) in MDA-MB-231 cells over a period of a maximum of 4 months of treatment. In this study therefore, it appears there may have been an underlying effect, likely the cause of cell death in the final stage of this experiment, that affected the development of chemoresistance. The slight increase in expression seen after the initial treatment of ABCC2 and ABCG2 could indicate that the process simply was not conducted over a long enough time period and that a significant effect may have been more likely if more allotment of time was given to this experiment. Conclusively, there is a definite and significant effect on the expression levels of genes relating to the expression of certain elements of transport witnessed. The link between treatment and chemotherapeutic resistance development is a developing study that needs further study. Experimentation observing the effects observed in relation to the increased expression of ABCC2 and ABCG2 as well as confirmatory studies to solidify findings through use of a MTT assay should be considered in future studies.
Keywords: TNBC; Breast Cancer; Doxorubicin; DOX; MDA-MB-231; Cell culture; Gene expression; RT-qPCR; Chemotherapy